To What Extent do Female Body Representations Create an Intersectional Understanding of Media Discourse? (Global Journal of Human-Social Science, 2023)
Despite media significance a lot still needs to be learned about how women s bodies are re presented in media narratives and the ensuing implications of these representations for women s health The construction of a uniform socio-culturally feminine image regime of truth owing to the feminine body shape standard evolved due to mainstream Western media s fascination with a slender female physique Aapola et al 2005 In our culture those who do not adhere to such aesthetic standards are often left out of discussions about feminine identity Duncan 1994
Keywords: female body; media; representation; socio-cultural discourse; identity